Mätegenskaper för fruktsamhet och modersegenskaper i fåraveln - Skogar, Anna (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2008)
The aim of this literature review was to suggest suitable index traits to use in the Swedish Sheep Recording Scheme for fertility and maternal traits. Since fertility and some of the maternal traits are not normally distributed advanced methodology is needed to calculate genetic parameters. Breeding is a tool to improve the economy of the farm and for the selection of breeders estimated breeding values (EBV) for important traits are of high value. In sheep breeding both lambs born and lambs weaned should be taken into consideration as well as the ewe's maternal ability, which includes lambing ease, lamb survival, ewe behaviour as mother and the early growth of the lambs. The measurements should be reliable and easy to perform on the farm and good guidelines on when and how they should be done must be spread. Unfavourable correlations have been found among various fertility and survival traits and also between fertility and other ewe traits. For example breeding for improved fertility might give rise to heavier ewes. In the genetic evaluation the index traits must be adjusted for environmental factors such as the age of the ewe and lambing season. Further investigations are needed to build up a genetic evaluation to be used for sheep in Sweden.